Design and Construction Risk Management of Souq Waqif Station of Gold Line, Doha Metro - Konstantis, Spyridon; Massinas, Spyros (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
The case of redesigning Souq Waqif station by raising the base slab formation level due to significant water inflow during the excavation and dewatering works and the break in activities of two EPB TBMs under adverse hydrogeological conditions is presented. The station is at close proximity with a structure of great heritage value and the monitoring records prior to TBM break in, indicated unacceptable ground deformation values. Back analyses were performed and contingency measures defined and implemented on site. The station redesign had also to take into consideration an adjacent future development affecting the station, the design basement levels of which increased during the station excavation.